2021
DOI: 10.3390/jcm10132967
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Uncontrolled Eating after Bariatric Surgery: The Role of Excessive Skin and Body Image Shame

Abstract: Excess skin and disordered eating behaviors are referred to as some of the major negative consequences of bariatric surgery as well as body image shame. This study sought to explore how discomfort with excessive skin, body image shame, psychological distress, eating-related psychopathology, and negative urgency interact to understand uncontrolled eating among woman submitted to bariatric surgery. A cross-sectional sample of 137 women was evaluated postoperatively through self-report questionnaires assessing di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
1
2
0
2
Order By: Relevance
“…Regarding inconveniences caused by ES, quantitative and qualitative findings both aligned with past studies [5][6][7] and offered similar insights; that, it is associated with body image factors such as social physique anxiety and body esteem. While there is evidence that MBS can improve some dimensions of body image, it is a complex and multidimensional concept, and accordingly not all dimensions may improve post-MBS [30], especially for individuals experiencing greater inconveniences caused by ES.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Regarding inconveniences caused by ES, quantitative and qualitative findings both aligned with past studies [5][6][7] and offered similar insights; that, it is associated with body image factors such as social physique anxiety and body esteem. While there is evidence that MBS can improve some dimensions of body image, it is a complex and multidimensional concept, and accordingly not all dimensions may improve post-MBS [30], especially for individuals experiencing greater inconveniences caused by ES.…”
Section: Discussionsupporting
confidence: 78%
“…Because negative body image factors relate to depressive symptoms and eating disorders, both associated with weight regain in past studies [6,7] and alluted to by focus group participants, mental health support is needed to deal with important and rapid body changes post-MBS.…”
Section: Discussionmentioning
confidence: 99%
“…Research showed associations between obesity, shame and stigmatization [ 1 ], but the bariatric field has mainly studied shame in combination with excess skin [ 25 ] and weight regain, two potential postoperative consequences. The single study that did assess this association reported no association between shame and weight loss [ 25 ]. The current results need replication.…”
Section: Discussionmentioning
confidence: 99%
“…Corroborando os achados Poulsen et al( 2016), em uma entrevista com 49 pacientes submetidos a cirurgia de contorno corporal, constataram que 36 deles apresentaram melhoras significativas após a realização das plásticas. Muitos relataram não ter consciência da intensidade da insatisfação do excesso de pele 6 . e a relação negativa com sua autoimagem 21 .…”
unclassified
“…e a relação negativa com sua autoimagem 21 . Tal fato ocorre devido à vergonha de seus corpos após a perda de peso extrema, com limitações da exposição em ambientes públicos em razão do excesso de pele 6,16 . Foi observado uma melhora na autoestima e autoconfiança em pacientes que realizaram a cirurgia de contorno 16,21 .…”
unclassified